Macrophage-derived nitric oxide initiates T-cell diapedesis and tumor rejection. (2nd October 2016) - Sektioglu, Ibrahim M.; Carretero, Rafael; Bender, Noemi; Bogdan, Christian; Garbi, Natalio; Umansky, Viktor; Umansky, Ludmila; Urban, Katharina; von Knebel-Döberitz, Magnus; Somasundaram, Veena; Wink, David; Beckhove, Philipp; et al.
ABSTRACT: In tumor biology, nitric oxide (NO) is generally regarded as an immunosuppressive molecule that impedes T-cell functions and activation of endothelial cells. Contrasting with this view, we here describe a critical role for NO derived from inducible nitric oxide (iNOS)-expressing tumor macrophages in T-cell infiltration and tumor rejection as shown by iNOS gene deletion, inhibition of iNOS, or NO donors. Specifically, macrophage-derived NO was found to induce on tumor vessels adhesion molecules that were required for T-cell extravasation. Experiments with human endothelial cells revealed a bimodal dose-dependent effect of NO. High doses of NO donors were indeed suppressive but lower, more physiological concentrations, induced adhesion molecules in an NFkB-dependent pathway and preferentially activated transcription of genes involved in lymphocyte diapedesis. iNOS + macrophages in tumors appear to generate precisely the amount of NO that promotes endothelial activation and T-cell infiltration. These results will be valuable for the development of strategies designed to overcome the paucity of T-cell infiltration into tumors that is a major obstacle in clinical cancer immunotherapy.